2017
DOI: 10.1128/aem.02736-16
|View full text |Cite
|
Sign up to set email alerts
|

Benzoate- and Salicylate-Tolerant Strains of Escherichia coli K-12 Lose Antibiotic Resistance during Laboratory Evolution

Abstract: Escherichia coli K-12 W3110 grows in the presence of membrane-permeant organic acids that can depress cytoplasmic pH and accumulate in the cytoplasm. We conducted experimental evolution by daily diluting cultures in increasing concentrations of benzoic acid (up to 20 mM) buffered at external pH 6.5, a pH at which permeant acids concentrate in the cytoplasm. By 2,000 generations, clones isolated from evolving populations showed increasing tolerance to benzoate but were sensitive to chloramphenicol and tetracycl… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

10
45
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 39 publications
(57 citation statements)
references
References 91 publications
10
45
1
Order By: Relevance
“…In fact, more than half the isolates sequenced had one of seven different mutations within the slp-gad island (Table S1). Large deletions were likely mediated by upstream insertion sequences, a common finding in stress evolution experiments (18,23). Thus, our early-generation sequences confirmed that the loss of Gad acid resistance was strongly selected by benzoate.…”
supporting
confidence: 76%
See 4 more Smart Citations
“…In fact, more than half the isolates sequenced had one of seven different mutations within the slp-gad island (Table S1). Large deletions were likely mediated by upstream insertion sequences, a common finding in stress evolution experiments (18,23). Thus, our early-generation sequences confirmed that the loss of Gad acid resistance was strongly selected by benzoate.…”
supporting
confidence: 76%
“…The MdtEF-TolC complex exports antibiotics from the cytoplasm, driven by PMF. Our benzoate-evolved isolates (18) have acquired point mutations or deletions throughout the slp-gad island, as well as knockout or point mutations in emrA, encoding the membrane fusion protein component of the EmrAB-TolC MDR pump (37,38); mdtA (39,40); and emrY (41). Other mutations affect genes for MDR regulators, such as cpxA (42), ariR (43), arcA (44), and rob (45).…”
mentioning
confidence: 99%
See 3 more Smart Citations